IDDF2018-ABS-0001 Foreign body ingestion: 4 cases with different management approach. (June 2018) - Gupta, Garima; Kumar, Deepak; Jhamb, Urmila
Abstract : Background: We managed four cases of ingested foreign bodies located in oesophagus and stomach differently. There are specific guidelines for the management of FB ingested in paediatrics age group depending upon type, size, symptoms and location in the digestive tract. Methods: Our first two cases were of ingested button battery which is blunt or non-sharp type contain corrosives, small in size (<2 cm diameter) and were impacted in the oesophagus, both the patients presented to us late by day 4 and 5. Both presented with symptoms of a cough, dysphagia, vomiting and respiratory distress later diagnosed tracheoesophageal fistula and needed surgical correction. Our third case was a 5 years old patient who had ingested a coin, which is blunt in type, was exactly 2 cm in diameter and was located in the stomach. As per guidelines he was followed serially for location by X-ray and symptoms but was later removed endoscopically, as coin had not passed the stomach outlet by the 4th week and had a risk of mucosal injury, although the patient was asymptomatic. Our fourth case had ingested small blunt plastic toy part which was initially impacted in oesophagus before referred to us. FB was tried to be removed endoscopically from oesophagus as soon as diagnosed with X-ray but was pushed down to the stomach during the procedure. In this case, the patient was further observed by us since the FB reached the stomach which was later found passed spontaneously in stool on day 6 after endoscopic failure. Results: With reference to our cases, we review the management protocols for ingested FB in paediatrics patients. Conclusions: Urgent Endoscopic removal (within 2 hours) is indicated in- • All symptomatic patients • Sharp foreign body • Esophageal foreign body • Foreign body in the stomach if- Age <5 years- >2 cm in diameter and >5 cm in length Age >5 years- >2.5 cm in diameter and >6 cm in length Non urgent endoscopic removal should be followed in- • Magnetic foreign bodies within 24 hours • Ingested button batteries in stomach impacted for >48 hours • Blunt small nontoxic foreign body in the oesophagus for more than 24 hours.